2017
DOI: 10.1158/0008-5472.can-16-3130
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics-Based Mathematical Modeling Identifies an Optimal Protocol for Metronomic Chemotherapy

Abstract: Metronomic chemotherapy is usually associated with better tolerance than conventional chemotherapy, and encouraging response rates have been reported in various settings. However, clinical development of metronomic chemotherapy has been hampered by a number of limitations, including the vagueness of its definition and the resulting empiricism in protocol design. In this study, we developed a pharmacokinetic/pharmacodynamic mathematical model that identifies the most effective administration schedule for gemcit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…For example, in “adaptive therapy”, the initial dose of an anti‐cancer drug is high and then the dosage is decreased as the tumor shrinks to eventually maintain the sensitive clone at a level sufficient to suppress the growth of the resistant clone . Similarly, in “metronomic therapy” an anti‐cancer drug is continuously administered in a low dose . Treatment regimens using a combination of drugs are also proposed as exemplified by “double bind therapy.” In this therapy, 2 different kinds of drugs are administered alternately to expose each of the 2 clones to their respective effective drugs, which can theoretically keep the tumor volume at a constant level .…”
Section: Perspectivementioning
confidence: 99%
“…For example, in “adaptive therapy”, the initial dose of an anti‐cancer drug is high and then the dosage is decreased as the tumor shrinks to eventually maintain the sensitive clone at a level sufficient to suppress the growth of the resistant clone . Similarly, in “metronomic therapy” an anti‐cancer drug is continuously administered in a low dose . Treatment regimens using a combination of drugs are also proposed as exemplified by “double bind therapy.” In this therapy, 2 different kinds of drugs are administered alternately to expose each of the 2 clones to their respective effective drugs, which can theoretically keep the tumor volume at a constant level .…”
Section: Perspectivementioning
confidence: 99%
“…Metronomic regimens are based upon the administration of small doses of cytotoxics over a long period of time with few or no breaks-a definition far too vague, requiring PK/ PD modeling to precisely define optimal dosing and scheduling. 101 Model-driven metronomics has been used next to determine optimal dosing and scheduling of gemcitabine in resistant neuroblastoma-bearing mice 102 and further used to set up metronomic regimens of oral vinorelbine in lung cancer patients. 103 Beyond canonical cytotoxics, PK or PK/PD models can be used to customize dosing of a wide variety of oral targeted therapies as well.…”
Section: Developing Smart Delivery Systemsmentioning
confidence: 99%
“…Ciccolini et al developed a pharmacokinetic/pharmacodynamic mathematical model that identified in silico the most effective administration schedule for gemcitabine monotherapy in chemoresistant neuroblastoma bearing mice. Based upon four biological assumptions regarding the mechanisms of action of metronomic chemotherapy, simulations identified that daily 0.5‐1 mg/kg gemcitabine was an optimal protocol to maximize antitumor efficacy, and that this regimen of gemcitabine significantly inhibited tumor angiogenesis and reduced tumor perfusion and inflammation in vivo, while standard gemcitabine did not …”
Section: Modern Dose Calculation—computational Mathematicsmentioning
confidence: 99%
“…Based upon four biological assumptions regarding the mechanisms of action of metronomic chemotherapy, simulations identified that daily 0.5-1 mg/kg gemcitabine was an optimal protocol to maximize antitumor efficacy, and that this regimen of gemcitabine significantly inhibited tumor angiogenesis and reduced tumor perfusion and inflammation in vivo, while standard gemcitabine did not. 45…”
Section: Modern Dose Calculation-computational Mathematicsmentioning
confidence: 99%